Sir John Boardman, James Hargrave, Alexander Avram, Alexander Podossinov, Connecting the Ancient West and East: Studies Presented to Prof. Gocha R. Tsteskhladze. - Kendall, Richard (Journal of Greek Archaeology, 2023)
pp. xliv, 1525 Leuven: Peeters, 2022. ISBN 9789042944138. €380.00.